Pandemic Elections and the Covid-Safe Effect: Incumbents Re-elected in Six Covid-19 Safe Havens - John Paull (Journal of Social and Development Sciences, 2021)
The Antipodes have been amongst the safest places on the planet during the Covid-19 pandemic. The governments of Australia and New Zealand (national, state, and territory governments) have acted promptly, decisively, and cohesively in closing borders, quarantining incoming returnees, instigating rigorous contact tracing and extensive testing, social distancing, hand washing, masks, and occasional lockdowns. Antipodean governments and populations have long experience of awareness and compliance with biosecurity issues. Isolation and distance have long served to keep Australia and New Zealand free of many pests and diseases. Each Antipodean election held during the Covid-19 pandemic has returned the incumbent. During the first 14 months of the pandemic, six out of six incumbent governments facing elections during the Covid pandemic have been returned. Five returned incumbents were center-left while the sixth was center-right. Four of the elections have rewarded the incumbent government with an increased majority, the Northern Territory election returned a reduced majority, and the Tasmanian election returned the status quo with the narrowest of majorities maintained. The New Zealand election returned the Labor government to power in their own right and released them from the coalition. The Western Australian election saw Labor returned with a landslide result with an unprecedented, win of 53 out of 59 seats (90% of seats). The object of the present paper is to report the outcomes of the six antipodean elections conducted during the Covid-19 pandemic (to date) and to reflect on the Covid-safe effect on them if any.